Moderasi Beragama dan Dialektika Akademik: Tren Kajian Moderasi Beragama di Indonesia selama Covid-19 - Wahab, Muhammad Royyan Nafis Fathul (NALAR, 2022)
This study aims to provide a critical exploration and conceptual summary of the broad academic landscape regarding the implementation of religious moderation that has been carried out in Indonesia, especially during the Covid-19 period. This study used the systematic literature review (SLR) method and found 887 articles relevant to the theme of religious moderation between 2020 and 2022. After screening, 28 articles were found, which were then reviewed. Qualitative theme analysis was then carried out using the NVivo 12 Plus software based on the specified articles. This study found that during the period 2020-2022, only 28 empirical studies from 887 published research regarding the implementation of religious moderation during the Covid-19 period in Indonesia. Most research locations were found in Central Java Province, with a literature percentage of 25%. The trend was mainly carried out in 2021, with a ratio of 53.57%, and was dominated by qualitative research, with a percentage of 96.42%. Moreover, this study found two themes: religious moderation activities (n=14) with nine sub-themes and religious moderation education (n=14) with seven sub-themes. This research provides theoretical and practical contributions as an offer in policy-making for implementing religious moderation in Indonesia and shows various sub-themes of religious moderation that can be carried out in future research.Keywords :